A Structural Contingency Approach to Bureaucracy and Democracy in U.S. National Unions - Jarley, Paul; Fiorito, Jack; Delaney, John Thomas (Academy of Management Journal, 1997)
Drawing on industrial relations and organizational science concepts, in this article we apply elements of contingency theory to national unions' representative and administrative structures. We argue that these structures are distinct and develop in response to different organizational and environmental imperatives. These ideas were tested with a unique set of data on unions' characteristics and environments. The results provide broad support for our approach and suggest that greater collaboration among industrial relations and organizational science scholars would benefit both literatures.